Molecular biological characteristics of Candida albicans strains causing recurrent vulvovaginal candidiasis with different susceptibility to antifungal drugs in vitro - Venchakova V.V.; Oganesyan E.G.; Guseva A.O.; Kovyrshin S.V.; Rusetskaya E.V.; Marochkovich O.A.; Dolgo-Saburova Yu.V.; Bogomolova T.S.; Zhang F.-M.; Meng Q.; Vasilyeva N.V.; Taraskina A.E. (Клиническая микробиология и антимикробная химиотерапия)
Objective.